Research on the technology of unloading pressure and preventing punching in extra-thick coal seams - Lixin Zhang; Zehui Deng; Gang Li; Guangchao Liu; Xu Lian (Scientific Reports)
Abstract This study addresses stress concentration in roadways and elastic energy accumulation in the cantilever beam of hard roofs within the goaf of extra-thick coal seams. Using the 61,607 working face of Longwanggou Mine as a case study, the key roof layer was identified through theoretical calculations, and hydraulic fracturing parameters were optimized via zoning and grading. Stress changes, displacement, and fracture distribution in the downtrack and retreat areas were analyzed using 3DEC software before and after fracturing. Microseismic monitoring evaluated energy and frequency of microseismic events, while borehole imaging observed post-fracturing fracture distribution. Results show that hydraulic fracturing reduces peak compressive stress from 34.8 to 19.2 MPa, representing a 44.8% reduction, and tensile stress in the mined-out void from 12.7 to 5.8 MPa, marking a 54.3% reduction. The high-stress concentration zone shrank from 68 to 20 m, corresponding to a 70.6% reduction, improving stress redistribution and structural stability. Roof subsidence increased by a factor of 1.96 to 2.07, facilitating earlier and more uniform subsidence of the hard rock layer and reducing overhang risks. Microseismic events with energy levels of 9500 J or greater decreased by 79%, confirming effective stress relief. Borehole imaging verified that hydraulic fracturing induced new fractures and expanded existing ones in the hard roof, disrupting its integrity, reducing seismic risks, and improving mining safety.